Pengaruh Proses Rekruitmen Terhadap Kinerja Dengan Penempatan Kerja Sebagai Variabel Intervening Pada Politeknik Negeri Bengkalis - Permatasari, Evi (Program Studi Manajemen FEBM UMRAH, 2023)
This research aims to determine the effect of the recruitment process on performance with job placement as an intervening variable. This research is located at Bengkalis State Polytechnic. The type of research is explanatory research with a quantitative approach by prioritizing questionnaires or questionnaires as a data collection tool and the data that has been collected is then used as material to analyze the empirical conditions of the objectivity of the research objectives at the location that will be used as the research site.. There are two population and sample groups in this research, namely lecturers who serve as heads of departments and heads of study programs and lecturers (teaching staff) with a total sample of 68 people. Data analysis techniques using SmartPLS 4.0 were used to test validity and reliability, R Square, f-Square, t-test, and path coefficient. Based on the results of the path coefficient for the influence of the recruitment process on performance, it is 0.351 P Values 0.035 < 0.05 T Statistics 2.105 > 1.96 so it can be concluded that the recruitment process significantly affects performance. The influence of the recruitment process on job placement is 0.504, P values 0.008 < 0.05, T statistic 2.636 > 1.96. The effect of work placement on performance is 0.521, P value 0.000 < 0.05, T statistic 3.905 > 1.96. The influence of the recruitment process on performance through job placement is 0.262, P value 0.036 < 0.05, T statistic 2.102 > 1.96. It can be concluded that the recruitment process has a significant influence on performance, the recruitment process has a significant influence on job placement, job placement has a significant influence on performance and the recruitment process has a significant influence on performance through job placement